The up and down spring - Hurwitz, Johanna; Owens, Gail (New York : Scholastic, 1993)
While vacationing at Bolivia's house in Ithaca, New York, eleven-year-old Rory tries to hide his fear of flying after Bolivia suggests a trip in her uncle's airplane.
Booklist.
Publisher's Weekly.
School Library Journal.
5.1
3-6
Keywords: Fear -- Fiction; Friendship -- Fiction; Fear -- Fiction; Friendship -- Fiction